Biological activities of Streptomyces sp. Bts40 isolated from the rhizosphere of Artemisia herba-alba Asso - Djemouai, Nadjette; Meklat, Atika; Gaceb-Terrak, Rabéa; Oulad Hadj Youcef, Khadidja; Nacer, Asma; Mokrane, Salim; Bouras, Noureddine; Verheecke-Vaessen, Carol (Universitatea din Oradea, 2022)
Actinobacteria isolated from the rhizosphere of plants are of interest as they produce a diverse range of molecules, such as antibiotics and enzymes. This study investigates the antibacterial activity, plant growth-promoting (PGP) abilities as well as the production of extracellular enzymes by the actinobacterial strain BTS40. This strain was isolated from the rhizospheric soil of the medicinal plant Artemisia herba-alba Asso that was naturally grown in a semi-arid environment. Morphological characteristics showed that the strain BTS40 belongs to the genus Streptomyces. Analysis of BTS40’s 16S rRNA gene sequence showed 99.45% similarity to Streptomyces alboniger NRRL B-1832T, in the EzTaxon database. This actinobacterium showed only antibacterial activity against Gram-positive bacteria. The strain also showed potential multiple traits for plant growth promotion and hydrolysis of enzymes. Hence, this study reveals that strain BTS40 has multiple PGP traits and produces many extracellular hydrolytic enzymes.
Keywords: Artemisia herba-alba; rhizosphere; Streptomyces; taxonomy; PGP; enzymes; semi-arid area; Algeria